Managing human capital in a knowledge based economy: The role of the HR function - Mohd.Yusoff, Yusliza; Abdullah, Hazman Shah (2008)
The emergence of the global economy, monumental improvement in information and communication technology, and the emergence of the knowledge economy are among the forces that are resulting in the transforming the Human Resources (HR)function. There is a growing consensus that human capital(HC) is critical to an organization’s success and that the HR focus must be more strategic in the new knowledge-based economy (K-economy)era. Knowledge economy and emphasis on HC provides opportunity for HR function to fundamentally alterits role in the corporation and become true value-adding partners.To achieve this HR, must understand the most valuable of organisational knowledge is embedded in the HC and it must creatively aid in its sustainable exploitation.